The prevalence of alcohol dependence and its association with hypertension: a population-based cross-sectional study4 in Xuzhou city, China - Ji, Ailing; Lou, Peian; Dong, Zongmei; Xu, Chunrong; Zhang, Pan; Chang, Guiqiu; Li, Ting (BMC public health, 2018)
To describe the prevalence of alcohol dependence and to explore the relationship between alcohol dependence and newly detected hypertension in China. A multistage stratified cluster sampling method was used to obtain samples from February to June 2013. The Michigan Alcoholism Screening Test was used to estimate alcohol dependence level. A standard questionnaire measured other independent variables. Enumeration data were analyzed using chi-square; quantitative data were analyzed using t-tests. Spearman correlation analysis and multivariate logistic regression analysis were performed to identify the relationship between alcohol dependence and hypertension. The alcohol dependence rate was 11.56%; 22.02% of males (3854/17501) and 1.74% of females (324/18656) were classified as alcohol dependent. The newly detected hypertension rate was 9.46% (3422/36157). Significant associations were found between alcohol dependence levels and blood pressure (P < 0.01). Alcohol dependence was positively correlated with systolic blood pressure (r = 0.071, P < 0.01) and diastolic blood pressure (r = 0.077, P < 0.01) and was an independent risk factor for hypertension after adjusting for confounders (low alcohol dependence: odds ratio [OR] = 1.44, 95% confidence intervals [CI] = 1.14-1.81, P < 0.01; light alcohol dependence: OR = 1.35, 95% CI = 1.11-1.64, P < 0.01; medium alcohol dependence: OR = 1.83, 95% CI = 1.40-2.41, P < 0.01). Alcohol dependence was high and associated with hypertension. Health education and precautions against alcoholism should be implemented in Xuzhou city.